The some problems of state registration in the field of the inherited legal relationships - Печений, О. П. (Theory and practice of jurisprudence, 2016)
In the article the problems of state registration are analysed as the multidimensional phenomenon which touches as civil laws, including a right on an inheritance, right of ownership, so legal facts. The questions of state registration are probed in the sphere of inheritance, in particular complications of decision of moment of origin of right of ownership on the real estate at an inheritance. Correlation of right is analysed on an inheritance and ownership rights.